Ethno-STEM Innovation in Science Learning: Developing Scientific Literacy Using the Local Context of “Dawet Jabung” - Muhammad Naqqi Imani; Wahono Widodo; Sukarmin Sukarmin; Muhammad Satriawan (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to analyze the effectiveness of a locally contextualized STEM-based learning device, “Dawet Jabung,” in improving students’ scientific literacy at MA Darul Huda. Methodology: A quasi-experimental posttest non-equivalent control group design was used. The experimental class (n = 16) learned using a STEM-based “Dawet Jabung” learning device, while the control class (n = 16) used traditional materials. Quantitative data were collected through a scientific literacy questionnaire and analyzed using descriptive statistics, independent-samples t-test, and N-Gain scores with SPSS 21. Qualitative data from interviews supported the quantitative findings. Main Findings: The experimental class showed higher scientific literacy, with 75% categorized as “good” and 25% as “very good” (M = 68), compared with the control class, which was dominated by the “poor” category (50%) with an average score of 58. The t-test revealed a significant difference (t = 9.297 > t-table = 2.036). The N-gain score of 0.65 indicated moderate effectiveness. Interview results indicated increased engagement, curiosity, and conceptual understanding among students who used the STEM tool. Novelty/Originality of this study: This study introduces a unique Ethno-STEM learning device integrating local wisdom “Dawet Jabung,” bridging scientific concepts with cultural practices. The innovation advances existing STEM literature by demonstrating that integrating cultural context enhances scientific literacy more effectively than conventional STEM alone. This work contributes a new pedagogical model aligned with the Merdeka Belajar curriculum’s emphasis on contextual and culturally responsive learning.